(untitled) (Economics and region, 2024)
The article examines the theoretical aspects of the formation of the company’s pricing policy, analyzes its formation, and develops measures for its optimization. The economic content of the price policy is disclosed, the internal and external factors affecting the formation of the price policy are characterized. It is noted that the price policy is the most important mechanism that ensures many priorities of the organization’s economic development. The article examines such issues as the peculiarities of the formation of the pricing mechanism, the elements of pricing, as well as its principles and tasks in the process of ensuring the competitiveness of the business entity. In the conditions of competition, the creation of a pricing mechanism and the identification of conditions that have a significant impact on setting the price of products are of particular importance. Pricing in a competitive environment should be focused on solving a single problem: to cover the cost of the product and bring sufficient profit, the price should be clear to the buyer and it should be competitive. It is very important to decide which direction will be chosen as part of pricing: costly, purchasing or competitive. Financial stability and competitiveness in the market depend on how correctly the company sets prices for its goods or services. The article examines the key properties of the competitiveness of domestic enterprises.